2020
DOI: 10.1186/s12935-020-01378-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TTN-AS1 promotes the progression of oral squamous cell carcinoma via miR-411-3p/NFAT5 axis

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a common kind of squamous cell carcinoma of the head and neck, which is a threat to public health. Long noncoding RNAs (lncRNAs) are associated with the development of various diseases, including cancers. LncRNA titin antisense RNA 1 (TTN-AS1) is known as a crucial regulatory factor in several cancers. Nevertheless, the specific functions of TTN-AS1 in OSCC remains obscure. Methods: The expression of TTN-AS1 in OSCC samples or cells was analyzed through qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…A great part of literature has pinpointed that lncRNA exerts various biological functions through binding with miRNA. 22 , 23 LncRNA PVT1 promoted cell growth and migration through competitively binding to miR-143 to modulates HK2 expression in gallbladder cancer. 24 In the current study, we identified that miR-214 is a target of MIR205HG from the Annolnc database.…”
Section: Discussionmentioning
confidence: 99%
“…A great part of literature has pinpointed that lncRNA exerts various biological functions through binding with miRNA. 22 , 23 LncRNA PVT1 promoted cell growth and migration through competitively binding to miR-143 to modulates HK2 expression in gallbladder cancer. 24 In the current study, we identified that miR-214 is a target of MIR205HG from the Annolnc database.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lncRNAs may play a role in carcinogenesis or tumor inhibition. For instance, suppression of TTN-AS1 resulted in an ability inhibition of OSCC cells in the tumor growth and metastasis via miR-411-3p/NFAT5 axis [32]. Overexpression of MCM3AP-AS1 promoted the proliferation and invasion of OSCC cells via regulating miR-204-5p/FOXC1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported mir-411-3p interacted with lncRNA ANRIL and inhibited the malignant proliferation and tumor stem cell like property of multiple myeloma (Wang et al, 2020). Another study demonstrated lncRNA TTN-AS1 could function as the mir-411-3p sponge in oral squamous cell carcinoma (OSCC) and mir-411-3p exerted the inhibitory functions on OSCC growth (Fu et al, 2020). In addition, lncRNA CDKN2B-AS1 could interact with mir-411-3p and contribute to carcinogenesis in ovarian cancer (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%